2024
DOI: 10.1038/s41598-023-50040-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chlorella vulgaris, Nannochloropsis salina, and Arthrospira platensis as bio-stimulants on common bean plant growth, yield and antioxidant capacity

Fatma Abd El Lateef Gharib,
kholoud Osama,
Amira Mohamed Abd El Sattar
et al.

Abstract: The use of bio-stimulants in agriculture has emerged as a promising strategy to improve crop growth and yield. One type of bio-stimulant that has gained attention is microalgae extracts, which are known for their high metabolic activity, bioactive compounds, and ability to enhance plant growth and development. To investigate their effectiveness, a pot experiment was conducted at the Experimental Farm of Helwan University in Egypt during the 2022 season. The experiment aimed to evaluate the efficacy of Chlorell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
(87 reference statements)
1
3
0
Order By: Relevance
“…A significant enhancement in flag leaf agronomic features upon the administration of S. platensis aqueous extract (SPAE) for both unstressed (SPAE-Cont treatment) and stressed (SPAE + DS) plants was noted in both cultivars. This enhancement is consistent with previous studies showing that S. platensis can act as a biostimulant to enhance plant growth [ 68 ] and ameliorate stress [ 69 ]. The multifaceted benefits of the SPAE, even amidst water stress scenarios, can be ascribed to many intrinsic properties and external interactions.…”
Section: Discussionsupporting
confidence: 93%
“…A significant enhancement in flag leaf agronomic features upon the administration of S. platensis aqueous extract (SPAE) for both unstressed (SPAE-Cont treatment) and stressed (SPAE + DS) plants was noted in both cultivars. This enhancement is consistent with previous studies showing that S. platensis can act as a biostimulant to enhance plant growth [ 68 ] and ameliorate stress [ 69 ]. The multifaceted benefits of the SPAE, even amidst water stress scenarios, can be ascribed to many intrinsic properties and external interactions.…”
Section: Discussionsupporting
confidence: 93%
“…Also, microalgae contain a large group of photosynthetic microorganisms that can produce diverse antioxidant components and colonize harsh environments, and several species of microalgae are known as important biostimulants due to their rich composition in phenolics, polysaccharides, phytohormones, fatty acids, chlorophyll, vitamins, and carotenoids [ 371 ]. Microalgal metabolites have been found to impact resistance to plants against abiotic stress, improve soil fertility, improve nutrient uptake from soil, and increase defense response against infection and pathogens [ 372 ]. It is also important to consider the important of Azotobacter due to its high plant growth promotion activities, nitrogen fixation, heavy metal tolerance, growth hormone production, and pesticide degradation [ 373 , 374 ].…”
Section: Stenotrophomonasmentioning
confidence: 99%
“…Numerous compounds, such as phenolics and ascorbate, have antioxidant activity that, in addition to increasing tolerance to stress, enhance the nutritional quality of crops [44]. Various studies have found that the application of biostimulants derived from algae can increase the accumulation of these types of compounds and the global antioxidant capacity [45][46][47]. The results of the present experiment suggest that it was mainly the application of the 3 mL L −1 dose of the Green Leaves product that produced a higher foliar concentration of total phenols and anthocyanins, followed by the application of Green Leaves at the 5 mL L −1 dose, with an increase in their levels when both doses were applied compared with the control plants.…”
Section: Antioxidant Compounds and Capacitymentioning
confidence: 99%